2012
DOI: 10.1007/s11255-012-0130-3
|View full text |Cite
|
Sign up to set email alerts
|

Elevated neutrophil to lymphocyte ratio predicts overall and cardiovascular mortality in maintenance peritoneal dialysis patients

Abstract: Neutrophil to lymphocyte ratio is a strong predictor for overall and cardiovascular mortality in PD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 22 publications
3
44
1
1
Order By: Relevance
“…Apart from vascular calcification, previous studies suggested that inflammation indicated by a higher level of CRP or the counts of white blood cells might be associated with elevated ALP and then participate in higher mortality (3,20,21). N/L is widely used as a marker of inflammation and a strong predictor for overall and cardiovascular mortality in PD patients (22). Our results also showed a positive correction between ALP and CRP as well as the N/L level ( Table 2).…”
Section: Discussionsupporting
confidence: 70%
“…Apart from vascular calcification, previous studies suggested that inflammation indicated by a higher level of CRP or the counts of white blood cells might be associated with elevated ALP and then participate in higher mortality (3,20,21). N/L is widely used as a marker of inflammation and a strong predictor for overall and cardiovascular mortality in PD patients (22). Our results also showed a positive correction between ALP and CRP as well as the N/L level ( Table 2).…”
Section: Discussionsupporting
confidence: 70%
“…An et al found that the NLR was an independent predictor of all causes of mortality as well as cardiovascular mortality in peritoneal dialysis patients, and patients with a higher NLR showed significantly increased overall and cardiovascular mortality rates compared to patients with lower NLR. 15 We found a significant correlation between the RV/LV short-axis ratio and NLR in our study.…”
Section: Discussionsupporting
confidence: 65%
“…23 One previous study reported that NLR43.5 was associated with an increase in the risk of cardiovascular and all-cause mortality in peritoneal dialysis patents. 13 Two studies have subsequently reported NLR 43.76 and 3.72 to be significant and independent (of CRP) predictors of cardiovascular events in pre-dialysis and dialysis-dependent patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Despite this, few studies have investigated the prognostic value of NLR in patients with chronic kidney disease, with none focusing solely on hemodialysis patients. 12,13 The aims of this study were to explore the relationship between NLR and other biochemical parameters, and to examine the value of NLR as a predictor of cardiovascular and all-cause mortality in hemodialysis patients.…”
Section: Introductionmentioning
confidence: 99%